Minimally invasive aortic root surgery: Midterm results in a 2‐year follow‐up. Issue 7 (22nd May 2020) - Elghannam, Mahmoud; Aljabery, Yazan; Naraghi, Hamid; Moustafine, Vadim; Bechte, Matthias; Strauch, Justus; Haldenwang, Peter
Abstract: Objectives: Minimally invasive surgery (MIS) via partial upper sternotomy (PUS) for aortic root surgery represents an alternative to the full median sternotomy (FMS). PUS offers less operative trauma. We analyzed the midterm outcome of root replacement (Bentall) or valve‐sparing root replacement (David) via PUS to evaluate the safety of this access. Methods: Between November 2011 to April 2017, a total of 47 consecutive patients underwent aortic root surgery with aortic aneurysm and/or localized aortic dissection through Bentall or David operation through PUS mean age (57.9 ± 10.5 years). Bentall operation was performed in 36 patients (77%), whereas 11 patients (23%) received a David procedure. The outcome was carried out in 6‐months, 1‐year, and 2‐years‐follow up. Results: Mean operation time was 287.3 ± 72.6 minutes, mean cardiopulmonary bypass (CPB) time 174 ± 54.8 minutes, mean cross‐clamp time 133 ± 33.1 minutes. Rethoracotomy‐rate was (4.2%). Superficial wound healing disturbance was (2%) and no deep sternal infection or sternum instability occurred. Hospitalization‐and intensive care unit‐stay was 11.8 ± 4.4 and 1.9 ± 1.3 days with a total median ventilation‐time of 10 (IQR 7.5‐13.5) hours. There was no 30‐day‐mortality. After 2 years the total rate of mortality, major adverse cardiac and cerebrovascular events, and redo surgery was (6.3%, 4.2%, and 4.2%). Conclusions: Minimally invasive aortic root surgery via partial upper sternotomy could be a safe alternative to the full median sternotomy. It requires longer operative times but reduces postoperative morbidity with good postoperative outcome.